Carbon Dioxide vs. Air Insufflation for Pediatric Gastrointestinal Endoscopy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ji, Chunwang; Liu, Xue; Huang, Peng (Frontiers in Pediatrics, 2021)
Background: Carbon dioxide (CO2) insufflation during gastrointestinal (GI) endoscopic procedures has gained popularity in adults. However, its utility in paediatric patients is not known. The current review aimed to compare the efficacy of CO2 vs air insufflation for GI endoscopic procedures in paediatric patients. Methods: The electronic databases of PubMed, Embase, Scopus, and CENTRAL were searched from the inception of databases to 15th August 2020. Results: All randomised controlled trials (RCTs) comparing CO2 vs air insufflation for GI endoscopic procedures in paediatric patients were eligible for inclusion. Five RCTs were identified. Pooled analysis of data from 226 patients in the CO2 group and 224 patients in the air group revealed that patients receiving CO2 insufflation were at a lower odds of experiencing postoperative pain as compared to those undergoing the procedure with air (OR: 0.40; 95% CI: 0.19, 0.87; I2=62%; p=0.02). Descriptive analysis indicated no difference in the two groups for abdominal distention after the procedure. Two trials reported elevated CO2 in the study group but without any pulmonary complications. Bloating was reported by two studies and both reported significantly less bloating in the CO2 group. Conclusion: Our study indicates that the incidence of pain may be reduced with the use of CO2 insufflation in paediatric GI endoscopies without a significant risk of adverse events. However, current evidence is from a limited number of trials and not strong to recommend a routine of CO2 in paediatric gastroenterology practice. Further high-quality RCTs are required to supplement current evidence.